2015
DOI: 10.1038/ncomms6953
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB4 controls embryonic patterning via Akt signalling independently of glycolysis

Abstract: How metabolism regulators play roles during early development remains elusive. Here we show that PFKFB4 (6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 4), a glycolysis regulator, is critical for controlling dorsal ectoderm global patterning in gastrulating frog embryos via a non-glycolytic function. PFKFB4 is required for dorsal ectoderm progenitors to proceed towards more specified fates including neural and non-neural ectoderm, neural crest or placodes. This function is mediated by Akt signalling, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 56 publications
4
55
0
Order By: Relevance
“…Possible non-glycolytic functions for PFKP must therefore also be considered. It is potentially noteworthy that a non-glycolytic role in early dorsal patterning has recently been demonstrated for PFKFB4, one of five known isoforms of phosphofructokinase-2 (PFK-2) [67].…”
Section: (B) Copy Number Variant Analyses Identify Novel Heterotaxy Gmentioning
confidence: 99%
“…Possible non-glycolytic functions for PFKP must therefore also be considered. It is potentially noteworthy that a non-glycolytic role in early dorsal patterning has recently been demonstrated for PFKFB4, one of five known isoforms of phosphofructokinase-2 (PFK-2) [67].…”
Section: (B) Copy Number Variant Analyses Identify Novel Heterotaxy Gmentioning
confidence: 99%
“…Furthermore, WB showed that neither NES nor Sox10 was expressed when PI3K/Akt or MAPK/Erk1/2 pathway was blocked. The effect of Akt pathway in pluripotency has been recently discussed in the context of embryonic and progenitor cell differentiation patterns . Furthermore, activating MEK was shown to prolong the expression of pluripotency marker Sox3, a Sox family member that is also regulated by FGF signaling .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Akt pathway in pluripotency has been recently discussed in the context of embryonic and progenitor cell differentiation patterns. 29 Furthermore, activating MEK was shown to prolong the expression of pluripotency marker Sox3, 28 a Sox family member that is also regulated by FGF signaling. 30 On the other hand, inhibition of Rac had no effect on the number of NES+ cells after 8 days of induction.…”
Section: Discussionmentioning
confidence: 99%
“…1). In addition, phosphatidylinositol 3-kinase (PI3K), a kinase that activates AKT, regulates NC induction in Xenopus laevis, a species closely related to X. tropicalis, although the exact roles of PI3K in NC induction remain controversial (Geary and LaBonne, 2018;Pegoraro et al, 2015). We therefore asked if DDX3 KD interferes with the AKT-GSK3b signaling axis.…”
Section: Depletion Of Ddx3 Leads To Reduced Akt Activity and Akt-depementioning
confidence: 99%
“…The function of PI3K-AKT signaling in NC induction is controversial. While treatment of gastrula-stage X. laevis embryos with a PI3K inhibitor reduces the expression of NC markers, a constitutively active form of PI3K can also reduce NC markers induced by Pax3 and Zic1 in isolated X. laevis animal caps, which are thought to contain pluripotent stem cells (Buitrago-Delgado et al, 2015;Geary and LaBonne, 2018;Pegoraro et al, 2015). However, PI3K has AKT-independent function (Faes and Dormond, 2015), and the mechanisms underlying the possible roles of AKT in NC induction remains largely unknown.…”
Section: Akt Is a Key Regulator Of Wnt/b-catenin Signaling And Nc Indmentioning
confidence: 99%